Elaboración de una guía didáctica del centro histórico, para el área de simulación del laboratorio de interpretación turística, para la carrera de ingeniería, en ecoturismo de la Universidad Técnica de Cotopaxi (fase ii) - Peralvo Haro, Claudio Dario (2015)
The present investigation has as objective to elaborate a Didactic Guide to give to know the students of the Career of Engineering in Ecoturismo in way educational didactics, the tourist places of the Historical Center of I Remove where the information of the historical architecture the construction time is detailed. For this she was defined three chapters: I surrender I, it tries on the technical elements that it sustains the present investigation, as: concepts, antecedents of the Historical Centers and their importance. In the chapter II, it contains the methodology and the registration of the Humanity's cultural patrimony, by means of inventory records taking like reference the record of MINTUR, was carried out the summary of the information according to the routes that are established for I Remove Tourism, they registered 22 attractiveness of importance for the development of our country. Finally, we have the Chapter III, in this chapter the didactic guide was elaborated with programs of design graph that are good for the creation and animation of information to reproduce it through a video or in this case a didactic guide, in which the student can with easiness to navigate in the different screens that deploy the necessary information of the Historical Center.